Outcomes for patients with COVID‐19 admitted to Australian intensive care units during the first four months of the pandemic. Issue 1 (15th December 2020) - Burrell, Aidan JC; Pellegrini, Breanna; Salimi, Farhad; Begum, Husna; Broadley, Tessa; Campbell, Lewis T; Cheng, Allen C; Cheung, Winston; Cooper, D James; Earnest, Arul; Erickson, Simon J; French, Craig J; et al.
Abstract: Objectives: To describe the characteristics and outcomes of patients with COVID‐19 admitted to intensive care units (ICUs) during the initial months of the pandemic in Australia. Design, setting: Prospective, observational cohort study in 77 ICUs across Australia. Participants: Patients admitted to participating ICUs with laboratory‐confirmed COVID‐19 during 27 February – 30 June 2020. Main outcome measures: ICU mortality and resource use (ICU length of stay, peak bed occupancy). Results: The median age of the 204 patients with COVID‐19 admitted to intensive care was 63.5 years (IQR, 53–72 years); 140 were men (69%). The most frequent comorbid conditions were obesity (40% of patients), diabetes (28%), hypertension treated with angiotensin‐converting enzyme inhibitors or angiotensin II receptor blockers (24%), and chronic cardiac disease (20%); 73 patients (36%) reported no comorbidity. The most frequent source of infection was overseas travel (114 patients, 56%). Median peak ICU bed occupancy was 14% (IQR, 9–16%). Invasive ventilation was provided for 119 patients (58%). Median length of ICU stay was greater for invasively ventilated patients than for non‐ventilated patients (16 days; IQR, 9–28 days v 3 days; IQR, 2–5 days), as was ICU mortality (26 deaths, 22%; 95% CI, 15–31% v four deaths, 5%; 95% CI, 1–12%). Higher Acute Physiology and Chronic Health Evaluation II (APACHE‐II) scores on ICU day 1 (adjusted hazard ratio [aHR], 1.15; 95% CI, 1.09–1.21) and chronic cardiac disease (aHR, 3.38; 95% CI, 1.46–7.83) were each associated with higher ICU mortality. Conclusion: Until the end of June 2020, mortality among patients with COVID‐19 who required invasive ventilation in Australian ICUs was lower and their ICU stay longer than reported overseas. Our findings highlight the importance of ensuring adequate local ICU capacity, particularly as the pandemic has not yet ended.